Reversibility of Singlet Oxygen Reactions with Acene-doped Conjugated Polymer Nanoparticles and Thin Films. - Zhang, Yimin. (Tufts Archival Research Center, 2017)
The detection of singlet oxygen is very important for understanding its mechanism of action in various chemical, biological, and therapeutic processes. Dialkynyl-substituted acenes react with singlet oxygen rapidly and the cyclo-reversion of the resulting endoperoxides has been well-documented in organic solution. The dialkynyl substitutions also enhances the oxidation stability of the acene and protects the resulting endoperoxides from thermal decomposition. However, the hydrophobic nature of acenes presents a challenge to their use in aqueous environments. This challenge can be overcome by incorporating the acene into fluorescent, water compatible conjugated polymer nanoparticles. Varying the doping percentages, we report the cyclo-reversion of the endoperoxide of 9,10-bis((4-methoxy-phenyl)ethynyl)anthracene (DE-ANT) when doped in poly(9,9-di-n-octylfluorenyl-2,7-diyl) (PFO, a fluorescent conjugated polymer) nanoparticles in water. However, the emission spectra of the nanoparticles suggests that full reversion of the endoperoxide to the parent acene is not occurring, so DE-ANT was doped into optically clear poly(methyl methacrylate) (PMMA) thin films to mimic the solid nanoparticle matrix, while simplifying the system to one chromophore to determine the underlying photochemical processes. Our results should be important for the future design of oxidation stable acene-based singlet oxygen detectors.